Hasan B. Musa el-Bani’nin Şerhu’l-Hikem isimli eserinin tahkik ve tahlili - Alkış, Abdurrahim (My University, 2003)
Dine kapsamlı bir bakış açısı olan tasavvuf, vahdet-i vücûd öğretisiyle varlıklara ve olaylara nasıl yaklaştığını ortaya koymuştur. Tahkîk ve tahlîlini ( edisyon kritik ) yaptığımız Hasan b. Mûsâ el-Bânî'nin Şerhu'l-Hikem isimli eseri bu alanda yazılmış önemli bir eserdir. Şerhi yapılan Hikem ismindeki eser vahdet-i vücûd anlayışının en önemli mümessillerinden Muhyiddin İbnu'l-Arabî'ye aittir. Bu eserde tasavvufun önemli meseleleri ile ilgili kısa ve özlü sözler bulunmaktadır. Hikemiyât türünden olan bu sözler şârih tarafından rivâyet ve dirâyet bakımından zengin bir şekilde şerhedilmiştir. Önemli birçok eseri olan Hasan b. Mûsâ'nın -bilinebildiği kadarıyla- inceleme konusu olan ilk eseri olması bakımından önemlidir. Ayrıca İbnu'l-Arabî'nin de Hikemine yazılmış ilk şerh olması da ehemmiyet arzetmektedir. Bu çalışmada eserin tahkiki ve tahlili yapılmış hikem ve hikemiyât, Hikemin müellifi İbnul'Arabî, anılan eseri, kitaba şerh yazan Hasan b. Mûsâ, eserleri ve Şerhu'l-Hikem isimli eseri hakkında bilgiler sunulmuştur. As a comprehensive approach towards the religion, has, with its teaching of Wahdet-i wucud, made it clear how it approaches beings and events. Hasan b. Musa el-Bânî's work, the Şarhu'l-Hikem on which we have conducted an overview and analysis, is one of the important works written in this field. The work called Hikam on which an assesment has been done, belongs to Muhyiddin İbnu'l-Arabi, one of the chief advocacy of the vahdet-i vücut approach. The work in question includes eloquent phrases regarding the important issues of mysticism. Belonging to Hikamiyât style, these phrases have been richly commented in terms of hearsay and competence by the commentator. The work in question is also important in the sense that -as far as known- it is the first, among Hasan b. Musa's many other important works, to be the issue of an analysis. Another point worth attention is that it is first şarh written to İbnu'l Arabi's Hikam. An overview and analysis of the book in question has been done in the current work, and information has been offered about hikem and hikemiyat, about Hikams author İbnu'l Arabi, about his mentioned book, and about Hasan b. Musa el-Bânî and his works, who wrote a comment to the book.
Keywords: Akâid ve Kelâm; Din; İslam; İslam Dini; Tasavvuf